Study of Irisin Hormone Level in Type 2 Diabetic Patients and Patients with Diabetic Nephropathy - Shelbaya, Salah; Abu Shady, Manal M.; Nasr, Merhan Samy; Bekhet, Meram Mohamed; Mageed, Yasmine Abd-Al; Abbas, Magdy (Current Diabetes Reviews, 2018)
Background: Type 2 diabetic patients with diabetic nephropathy are associated with multifactorial abnormal energy metabolism. Irisin has been recently introduced as a hormone that is exercise-induced and is secreted by skeletal muscles. It is hypothesized that patients with chronic kidney disease usually have abnormal irisin levels. Aim: We aimed to study the level of Irisin hormone in patients with type 2 diabetes and to document that it is related to diabetic nephropathy. Methods: The current study included 60 subjects with type 2 diabetes and 30 healthy subjects as a control group. Diabetic subjects were divided into 30 without diabetic complications and 30 with diabetic nephropathy (DN). Serum Irisin levels, fasting blood glucose (FBG), 2hours plasma glucose (2hPG), hemoglobin A1c (HbA1c), kidney functions including serum creatinine and albumin/ creatinine ratio were assessed. Results: There was a statistically significant decrease in Irisin levels in diabetic patients compared to controls (34.46 ± 15.28 ng/ml vs. 152.600 ± 39.581 ng/ml, p<0.001). Irisin levels were lower in diabetic patients with DN than in those without complications (20.967 ± 4.476 ng/ml vs. 47.967 ± 8.853 ng/ml, p<0.01). There was a statistically significant negative correlation between irisin and serum creatinine (r=-0.729), systolic blood pressure (r=-0.493), diastolic blood pressure (r=-0.625), duration of diabetes (r=-0.942), BMI(r=-0.396), albumin/creatinine ratio (r=-0.696), and HbA1c (r=-0.305) in all type 2 diabetic patients (p<0.05). On performing multivariate regression analysis, we found that the duration of diabetes was the only independent determinant of irisin level. Conclusion: There is a decrease in serum irisin level in type 2 diabetic patients with even more significant reduction in patients with diabetic nephropathy.
Keywords: HbA1c